Customer Preference Analysis on Tahu Benjo Product Attributes: Conjoint Approach - Ester Kurnianti; Nila A. Windasari (Riviera Publishing, 2025)
The growing popularity of plant-based snacks among Indonesian consumers—particularly Gen Z and Millennials—presents both opportunities and challenges for local brands. Tahu Benjo, a tofu-based snack brand in Solo, seeks to revitalize its market presence amid declining competitiveness. This study aims to identify the most preferred product attributes of Tahu Benjo using a conjoint analysis approach. Data were collected through an online survey completed by 191 respondents and analyzed using the Choice-Based Conjoint (CBC) method and the Multinomial Logit Model (MNL). The results indicate that packaging is the most important attribute (31%), followed by price (23%), cooking method (21%), ingredient composition (18%), and flavor (7%). The optimal product profile identified consists of a tofu-mushroom mix, savory flavor, fried preparation, eco-friendly packaging, and a price range of Rp 10,000–15,000. This configuration achieved the highest utility score and market preference. Based on these insights, strategic recommendations include launching a flagship product with the preferred attributes, reformulating underperforming SKUs, and implementing targeted digital marketing campaigns. The study contributes to consumer behavior literature in emerging plant-based markets and offers actionable guidance for brand repositioning.